PERANCANGAN UI/UX WEBSITE SEBAGAI MENDIA INFORMASI DI MAJELIS AL-KAROMAH KARANGWANGI - Muhammad Ibnu Sinna; Rifqi Fahrudin; Victor Asih; Marsani Asfi (Universitas Catur Insan Cendekia, 2026)
The development of digital technology has brought major changes in the way people access information, including in the realm of Islamic religion. Majelis Al-Karomah Karangwangi as an Islamic Religious Institution that is active in da'wah, learning, and social activities, requires digital media to expand the reach of information and increase congregation participation. Through this Final Project, an official website for Majelis Al-Karomah Karangwangi is designed to function as a visual communication media that is informative, responsive, and easily accessible to various groups. The design process was carried out using the Design Thinking method, starting from finding visual ideas, wireframe sketches, to creating interactive prototypes. The website content includes the profile of the assembly, flagship programs such as student recitation, tahlil, maulid, blessed pilgrimage, as well as documentation of activities presented visually and attractively. The final result of the UI/UX design of this Website is expected to strengthen the digital image of Majelis Al-Karomah Karangwangi, as well as become an effective means of da'wah and information in the modern era.